2008
DOI: 10.1016/j.technovation.2007.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Safeguarding SMEs dynamic capabilities in technology innovative SME-large company partnerships in South Africa

Abstract: This paper focuses on technological collaboration between small and large firms. It is argued that such collaborations can be beneficial for both types of partner, but that small firms often are confronted by the hazards of collaboration as these relationships are typically asymmetric. As a result of this, knowledge embodied in the dynamic (strategic, internal and external) capabilities of SMEs can flow unintentionally to the larger partner.If this occurs, the collaboration would be less successful from the SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 42 publications
0
60
0
5
Order By: Relevance
“…However, most of the literature on dynamic and organizational capabilities consists of descriptive studies rather than empirical findings [4,6,[14][15][16][17][18]. The majority of empirical studies are case studies [15,19,20]. Empirical studies that feature more quantitative approaches are still needed to provide more academic rigor to this concept, especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the literature on dynamic and organizational capabilities consists of descriptive studies rather than empirical findings [4,6,[14][15][16][17][18]. The majority of empirical studies are case studies [15,19,20]. Empirical studies that feature more quantitative approaches are still needed to provide more academic rigor to this concept, especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, innovation is very expensive for SMEs, given their constraints in terms of internal resources such as technology, finance, marketing and human resources (Kumar and Subrahmanya, 2010;Sawers et al, 2008). Consequently, the benefits from Aggelopoulos et al 41 innovation should clearly outweigh its costs and risks.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…That this is a relevant issue in the South African context is shown in several studies. Sawers, Pretorius and Oerlemans (2008) stated that there are unintentional knowledge flows from small and medium-sized enterprises (SMEs) to their larger partners in South Africa. In the study 'Industrial innovation in South Africa, 1998' by Oerlemans et al (2004, it is shown that many South African innovative firms benefit from this type of knowledge flow, which results in an imitation type of innovative behaviour.…”
Section: Intended and Unintended Knowledge Flowsmentioning
confidence: 99%